Investigation of the Relationship between Reverse Current of Crystalline Silicon Solar Cells and Conduction of Bypass Diode - Hong Yang; He Wang; Minqiang Wang (International Journal of Photoenergy)
In the process of crystalline silicon solar cells production, there exist some solar cells whose reverse current is larger than 1.0 A because of silicon materials and process. If such solar cells are encapsulated into solar modules, hot-spot phenomenon will emerge in use. In this paper, the effect of reverse current on reliability of crystalline silicon solar modules was investigated. Based on the experiments, considering the different shaded rate of cells, the relation between reverse current of crystalline silicon solar cells and conduction of bypass diode was investigated for the first time. To avoid formation of hot spots and failure of solar modules, the reverse current should be smaller than 1.0 A for 125 mm × 125 mm monocrystalline silicon solar cells when the bias voltage is at −12 V.